Late Glacial and Holocene Palaeolake History of the Última Esperanza Region of Southern Patagonia - Roberts, Stephen J.; McCulloch, Robert D.; Emmings, Joseph F.; Davies, Sarah J.; Van Nieuwenhuyze, Wim; Sterken, Mieke; Heirman, Katrien; Van Wichelen, Jeroen; Diaz, Carolina; Van de Vyver, Evelien; Whittle, Alex; Vyverman, Wim; et al. (Frontiers in Earth Science, 2022)
We undertook multi-proxy analyses on two sediment cores from Lago Pato, a small lake basin at 51°S topographically separated from Lago del Toro in Torres del Paine (TdP), to provide insights into glacier dynamics and lake-level change in the TdP and Última Esperanza region over the last ∼30,000 cal a BP (30 ka). Lago Pato is situated in a region overridden by the Southern Patagonian Ice Field during the Last Glacial and in a transitional climatic zone of Southern Patagonia sensitive to seasonal- to millennial-scale changes in the Southern Hemisphere Westerly Winds (SWW). Results show that a deep ice-dammed and enlarged palaeolake encompassed Lago del Toro and Lago Pato c. 30–20 ka after the ice had retreated from local-Last Glacial Maximum (l-LGM) limits at c. 48–34 ka and during the build-up to the global-Last Glacial Maximum (g-LGM), c. 26–19 ka. Gaps in both sediment records between c. 20–13.4 ka and c. 20–10 ka suggest hiatuses in sediment accumulation during the g-LGM and Antarctic Cold Reversal (ACR) readvances and/or removal by lake lowering or flushing during the Late Glacial–early Holocene. The palaeolake level dropped from >100 m a.s.l. to ∼40–50 m a.s.l. towards the end of the ACR c. 13.4–13.0 ka, creating a shallower glaciolacustrine environment dammed by an ice tongue in the Estancia Puerto Consuelo–Última Esperanza fjord. Further lowering of the enlarged palaeolake level occurred when the ice thinned to <40 m a.s.l., eventually isolating Lago Pato from Lago del Toro and glaciogenic sediment input at c. 11.7 ka. After isolation, the ecology and water levels in Lago Pato became sensitive to regional climate shifts. The shallow, stable, and highly anoxic environment that developed after c. 11.7 ka is associated with weaker (or poleward shifted) SWW at 51°S and was replaced at c. 10 ka by an increasingly productive shallow-littoral lake with a variable lake-level and periodic shifts in anoxic-oxic bottom water conditions and ratios of benthic-planktonic diatoms. A more open Nothofagus forest, established at c. 8.6–7.5 ka, and more arid conditions c. 7.5–5.7 cal ka BP are linked to another phase of weaker (or poleward shifted) SWW at 51°S. More persistently wet conditions from c. 5.7 ka, with extensive closed Nothofagus forests and planktonic diatoms dominant, are associated with stronger (or equatorward shifted) SWW over 51°S. The abrupt return of benthic-to-tychoplanktonic diatoms after c. 3 ka reflects enhanced SWW at 51°S. Increasingly stable lacustrine and littoral wetland conditions established in the last ∼500 years reflect weaker SWW and lasted until recent decades.